An Analysis of the Use of General Japanese and Tourism Japanese in the World of Work in the Hospitality Field in Hiroshima - Annisa, Shafa Zahra; Karnawati, Rita Agustina (KIRYOKU, 2024)
This study analyzes the differences between the use of general Japanese and tourism Japanese in the workplace in the hospitality industry in Hiroshima, Japan. The method used is descriptive qualitative with observation, interviews, and document analysis. The theory used is Register theory by Michael Haliday. The results of the study show that there are significant differences between general Japanese and tourism-related Japanese in the context of hospitality. Tourism Japanese tends to be more formal and polite, with the use of specific terms related to guest service and tourism. In addition, tourism language also emphasizes the accuracy of information and friendliness in communication, which are very important to increase guest satisfaction. This study is also useful for the development of language training in hospitality and helps tourism professionals in effective communication.Keywords: general japanese; tourism japanese; hospitality; professional communication